PENGARUH REBRANDING DAN STORE ATMOSPHERE TERHADAP MINAT BELI ULANG PADA LEGIT PAIT COFFEE SIDOARJO - Ardean Naufal Adyar; Hery Pudjoprastyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The coffee business in Indonesia has experienced significant expansion in recent years, including in Sidoarjo, where the number of coffee shops continues to increase. Legit Pait Coffee, previously known as Kedai 27 Sidoarjo, is rebranding to create a new, more unique identity with a Javanese concept, as well as making changes to the shop atmosphere to attract more consumers. This rebranding is expected to increase customer attraction and loyalty. This study utilizes the Partial Least Square (PLS) method to carry out hypothesis testing regarding the correlation between rebranding, store atmosphere and repurchase interest. This study utilizes primary data, namely respondents' answers from a sample of Legit Pait Coffee Sidoarjo consumers. The study findings show that rebranding and store atmosphere have a significant positive impact on consumers' repurchase interest.